Marangoni convection-driven laser fountains on free surfaces of liquids. (November 2021) - Lin, Feng; Quraishy, Aamir Nasir; Tong, Tian; Li, Runjia; Yang, Guang; Mohebinia, Mohammadjavad; Qiu, Yi; Vishal, Talari; Zhao, Junyi; Zhang, Wei; Zhong, Hong; Zhang, Hang; et al.
Abstract: It is well known that an outward Marangoni convection from a low surface tension region will make the free surface of a liquid depressed. Here, we report that this established perception is only valid for thin liquid films. Using surface laser heating, we show that in deep liquids a laser beam pulls up the fluid above the free surface generating fountains with different shapes, and with decreasing liquid depth a transition from fountain to indentation with fountain-in-indentation is observed. High-speed imaging captures a transient surface depression before steady elevation is formed, and computational fluid dynamics simulations reveal the underlying flow patterns and quantify the depth-dependent and time-resolved surface deformations. Systematic investigation of the effect of laser parameters, surface tension and area of the fluid on its surface deformation further confirms that the laser fountain is a result of dynamic competition between outgoing Marangoni convection and the upward recirculation flow. Experiments and simulations also reveal that a smaller surface area can dramatically strengthen laser fountain. The discovery of laser fountain and the development of related experimental and simulation techniques have upended a century–old perception and opened up a new regime of interdisciplinary research and applications of Marangoni-induced interface phenomena. Graphical abstract: Image 1 Highlights: Discovered laser-induced liquid fountain and elevation through thermocapillary Marangoni convection. Observed liquid depth-dependent surface deformation from depression to elevation with increasing liquid depth. Developed a CFD simulation model that solves surface deformation, flow and temperature of a liquid with arbitrary thickness. Developed new thermocapillary fluids that exhibit strong laser-induced fountains.